TLC-Densitometric Determination of Vitamins B1, B6 and B12 in Pure and Pharmaceutical Formulations Using Treated Aleppo Bentonite - Aziz Ramadan, Abdul; Bodakji, Amer; Mahmoud, Ibrahim (Asian Journal of Chemistry, 2010)
Determination of vitamins B1, B6 and B12 in pure and in pharmaceutical formulations by thin layer chromatography (0.30 mm thickness) using acid treated Aleppo bentonite and mobile phase consisted of isobutyl alcohol:methanol:chloroform:acetic acid:ammonia (7.5:1:3.5: 0.4:0.5, v/v/v/v/v)has been applied. The specific surface area of bentonite was 168.25 m2/g and mean pore size was 52.3 Å determined using nitrogen adsorption (BET). Quantification was carried out densitometerically at λ = 275 nm for vitamins B1, B6 and B12 ( if their concentrations are in close proximity) and at λ = 525 nm for vitamin B12 (when CB6 ≈ CB1 >> CB12 as in pharmaceutical products). This method is successful for vitamin B1, B6 and B12 formulation even in the ratios between vitamin B12 and others 1:100. The retardation factors (Rf) of B1, B6 and B12 were 0.37, 0.68 and 0.26, respectively. Calibration curves were obtained in the range of 5.0-40.0 μg/ spot for vitamins B1, B6 and B12 (at λ = 275 nm) for standard solutions, while for pharmaceutical products, vitamins B1, B6 were determined at λ = 275 nm and vitamin B12 was determined at λ = 525 nm in the range of 0.5- 4.0 μg/spot.